Structure, Meaning, and Cultural Values of Syair Mantau in the Kenduri Sko Traditional Ritual in Kerinci - Sherly Leola; Warni; Nazurty (Universitas Islam Negeri Palopo, 2025)
This study aims to examine the structure, meaning, and cultural values embedded in the oral tradition of Mantau, performed during the Kenduri Sko ritual in Lempur Tengah Village, Kerinci Regency. As a form of oral literature, Mantau consists of rhythmic poetic verses sung during the traditional Tauh dance. This research employs a descriptive qualitative method using a structuralist approach. Data were collected through direct observation, in-depth interviews with 12 informants—including Mantau performers, traditional leaders, and cultural experts—and documentation of three live performances over a three-month period. The analysis draws on theories of structuralism (Nurgiyantoro), meaning (Chaer; Abdullah), and cultural values (Djamaris). Findings reveal that Mantau lyrics possess distinct physical structures, including specific diction, rhyme, figurative language, and rich imagery. Internally, they reflect themes of gratitude, spirituality, social harmony, and moral values. The meanings conveyed span lexical, grammatical, and cultural domains, highlighting the Kerinci community’s worldview. The cultural values embedded in Mantau encompass religious devotion, harmonious coexistence with nature, social cohesion, and self-reflection. These findings underscore Mantau not merely as ritualistic entertainment but as a vital medium for intergenerational transmission of Kerinci identity and values, offering broader implications for oral literature preservation in a modernizing world.